The really mean jelly bean - Curtain, Sharon ([Gordon, New South Wales] : Xlibris, 2019)
"n a bowl full of colourful jelly beans, one jelly bean stands out-for all the wrong reasons. He is the mean jelly bean, and he spends his days tormenting and pushing the other jelly beans away. "You are a really mean jelly bean!" the other jelly beans say. But he just keeps on bullying. One day, the mean jelly bean looks around and finds no one left to push around. He's all alone in the candy bowl. What's a mean jelly bean to do? Can the kindness of the other jelly beans rub off on him?"--Booktopia.
For pre-school age.
Keywords: Bullies -- Juvenile fiction; Friendship -- Juvenile fiction; Jellybeans -- Juvenile fiction; Bullies; Friendship; Jellybeans; Australian; Fiction